2016
DOI: 10.3389/fpsyg.2016.01695
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Children Defy Majorities? The Role of Dissenters in Chinese and Spanish Preschoolers’ Social Judgments

Abstract: When many people say the same thing, the individual is more likely to endorse this information than when just a single person says the same. Yet, the influence of consensus information may be modulated by many personal, contextual and cultural variables. Here, we study the sensitivity of Chinese (N = 68) and Spanish (N = 82) preschoolers to consensus in social decision making contexts. Children faced two different types of peer-interaction events, which involved (1) uncertain or ambiguous scenarios open to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 46 publications
(67 reference statements)
2
22
1
1
Order By: Relevance
“…Of 4‐year‐olds, 40%–60% adapted their responses to those of the (incorrect) peer majority on visual and social‐conventional judgment tasks, despite knowing the correct solution (e.g., Haun & Tomasello, ; Kim, Chen, Smetana, & Greenberger, ). However, 60%–80% of preschoolers did not conform to a peer (or adult) majority when conformity contradicted a moral norm (Enesco, Sebastián‐Enesco, Guerrero, Quan, & Garijo, ; Engelmann, Herrmann, Rapp, & Tomasello, ).…”
Section: Influence Of Othersmentioning
confidence: 99%
“…Of 4‐year‐olds, 40%–60% adapted their responses to those of the (incorrect) peer majority on visual and social‐conventional judgment tasks, despite knowing the correct solution (e.g., Haun & Tomasello, ; Kim, Chen, Smetana, & Greenberger, ). However, 60%–80% of preschoolers did not conform to a peer (or adult) majority when conformity contradicted a moral norm (Enesco, Sebastián‐Enesco, Guerrero, Quan, & Garijo, ; Engelmann, Herrmann, Rapp, & Tomasello, ).…”
Section: Influence Of Othersmentioning
confidence: 99%
“…Other work has found that the role of the dissenter in social scenarios is related to the culture in which deference to the majori-anales de psicología, 2017, vol. 33, nº 1 (january) ty is explored (Enesco, Sebastián-Enesco, Guerrero, Quan, & Garijo, 2016). In a different line of results, some recent studies on other socio-conventional domains (i.e.…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 99%
“…In this type of context, the individual lacks information to assess or interpret a situation more fully. For example, Enesco, Sebastián‐Enesco, Guerrero, Quan, and Garijo () presented 4–6‐year olds a series of ambiguous peer interaction situations that could be interpreted in two different ways, either as an accident (e.g., the child fell off the swing) or as a malicious action (e.g., the child was pushed off the swing). Given these situations, the children were willing to trust the testimony of others in order to interpret what had happened.…”
Section: Introductionmentioning
confidence: 99%
“…However, the few studies carried out in cultures other than Anglo‐Saxon countries do not always confirm this general trend, and sometimes yield contrasting findings. For instance, Enesco et al () found that a majority of Chinese children accepted the criteria of a group of teachers who unanimously supported the exclusion of a peer (e.g., not letting a child play with the rest of the group) whereas Spanish children of the same age maintained their opposition to the exclusion, going against the teachers' unanimous opinion. However, interestingly, the children from both countries condemned the situation in the absence of testimonial information (Enesco et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation